Avaliação do desgaste de uma resina nanocerâmica após diferentes tratamentos de superfície com diferentes antagonistas - Doneda, Jadson Fernando Felini (2023)
The wear of materials is extremely important for all areas, covering several areas from engineering to health. In dentistry, wear is natural for humans, but this directly affects function and aesthetics. With the advancement of technology, more and more varieties of dental restorative materials appear, such as nanoceramic resin, and it is essential to understand their wear mechanisms. The objective of this dissertation was to investigate the wear behavior of a nano ceramic resin (RN) subjected to different surface treatments in an oral wear test using different antagonists, through an oral wear test. The methodology was carried out in three stages: preparation of test specimens (CPs), wear testing and analysis. 72 RN CPs were produced and divided according to surface treatment (n = 24): CAD - abrasion with sandpaper to simulate CAD/CAM; POL - polishing with Sof-Lex; GLA - application of a fluid resin (Optiglaze). The CPs were subdivided according to the wear test antagonist (n=12): (C) ceramic and (R) composite resin. The wear test was performed in a chewing simulator in water at 37°C, 49 N, 1 mm slip, 2 Hz, for 50,000 cycles. The surface roughness of the CPs was evaluated with a contact roughness meter. Images of the wear facets were obtained using a stereomicroscope and scanning electron microscope (SEM). The roughness and diameter data of the antagonist facet were analyzed with Kruskal-Wallis and Student-Newman-Keuls comparison test ( = 0.05). The length (mm) and width (mm) data of the facets were analyzed with two-way ANOVA and Tukey's test (¿=0.05). For the surface roughness parameters there was a statistical difference between the surface treatments (p<0.001), with CAD obtaining the highest values. For the length and width of the CP wear facet, there was statistical significance for the surface treatment factor (p<0.001), for the antagonist factor (p<0.050) and for the interaction between factors (p=0.001). The R antagonist showed the largest wear area when tested against the CAD group, followed by the POL and GLA groups. Antagonist C showed a larger wear area for the CAD and POL groups, and smaller for GLA. It was concluded that the type of surface treatment and antagonist affect the wear pattern of the RN.